I AND YOU AND THE DIVIDED I - Newland, Matthew (Science et Esprit)

(untitled) (Collège universitaire dominicain, Ottawa, 2021)
This paper re-examines Martin Buber’s idea of I-You relationships in light of what more contemporary science, biology, and sociology teach us about the human brain and its development. Because these new understandings of human beings, our relationships with one another, and the world we live in, make it more difficult to identify/label us and our relations into clear categories (“I” and “You,” or “It”), this essay aims to find a way to reconcile them with Buber’s thought. This paper shows how scientific discoveries regarding the brain and psychological models of the mind (both Plato’s, as found in the Republic, and those being described in present-day psychology) expand the ranges of beings/entities capable of entering into overlapping relationships.